Review: Spawning Induction in Bivalve - Ludi Parwadani Aji (Jurnal Penelitian Sains, 2011)
Spawning induction is eminent to bivalve hatchery production as it involves control of the timing of reproduction to make maximum fertilization. There is several ways to induce spawning in sexually mature bivalve which the major methods are chemical stimulation, biological stimulation and physical shock. Chemical induction can be obtained by using hydrogen peroxide, serotonin and sex steroids injection into the gonad or mantel of the broodstook. Biological stimulation is conducted by using microalgae as a diet for conditioning of adult bivalve and by introducing gonad extract into the medium or gonads of the broodstock. While, physical shock can be done by rapidly decreasing or increasing of salinity or temperature to mature bivalve. Physical shock was less efficient compare to chemical injections but still commonly used as it is less invasive and has been found to be quite effective in certain bivalves. In addition, using microalgae as a diet is mostly used for broodstook conditioning rather than to induce spawning. All and all, the different species of bivalve react differently depend on what spawning method is used.